Weather index insurance: lessons learned and best practices for Bangladesh. Workshop Report, 8-9 September 2013, Dhaka, Bangladesh - Ahmed, T.; Hasemann A (WorldFish, 2013)
WorldFish and the International Centre for Climate Change and Development (ICCCAD) held a two-day workshop on the topic of Weather Index-Based Insurance: Lessons Learned and Best Practices for Bangladesh. Weather index insurance is based on a predefined weather event which when triggered ensures automatic payout to farmers who have taken out insurance. For example, the climatic trigger could be a predefined consecutive number of days where rainfall is below a set level or when the floodwater level reaches above a certain point. Index insurance has been operating for about 10 years in many countries but is still at an early stage in Bangladesh, where there are two schemes currently being piloted and three other projects being developed. Further information can be found in the scoping report: Current Status of Index-Based Insurance in Bangladesh (http://www.worldfishcenter.org/resources/publications/scoping-reportcurrent-status-index-based-insurance-bangladesh), which was conducted to inform the design and objectives of the workshop.